PJMHS 2022
DOI: 10.53350/pjmhs221610572
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Follys Catheter Intrauterine Balloon Temponade for the Control of Postpartum Hemorrhage

Abstract: Objective: This research aims to determine how well balloon temponade works as a treatment for postpartum bleeding. Study Design: Retrospective Study Place and Duration: Gynaecology and Obstetrics Department, Combined Military Hospital, Peshawar for the duration from February 2021 to January 2022. Methods: Total 118 women had age 18-40 years were presented in this study. Patients who were diagnosed with, or who were admitted to the hospital for treatment of primary postpartum haemorrhage caused by uterine aton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…13,19 Mean gestational age was 38.2±3.2 weeks which is in line with the findings of Kadioglu et al, who found that the average duration of pregnancy was 37.9±3 weeks and also matched with findings of Lohano et al (2016), to be 37.81±1.67 years. 13,20 Mean blood loss was 1032.1±379.6 ml which was similar to study of Dawood et al (2022) who reported that the average amount of blood lost was 1208.5±227.9 ml and also related with findings of Lohano et al an average of 1155.8 ±350.6 ml of blood was lost per patient. 13,21 In our study mean parity was 4.1±1.3 which was comparable to findings of Lohano et al (2016) 3.41±1.3.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…13,19 Mean gestational age was 38.2±3.2 weeks which is in line with the findings of Kadioglu et al, who found that the average duration of pregnancy was 37.9±3 weeks and also matched with findings of Lohano et al (2016), to be 37.81±1.67 years. 13,20 Mean blood loss was 1032.1±379.6 ml which was similar to study of Dawood et al (2022) who reported that the average amount of blood lost was 1208.5±227.9 ml and also related with findings of Lohano et al an average of 1155.8 ±350.6 ml of blood was lost per patient. 13,21 In our study mean parity was 4.1±1.3 which was comparable to findings of Lohano et al (2016) 3.41±1.3.…”
Section: Discussionsupporting
confidence: 86%
“…13,20 Mean blood loss was 1032.1±379.6 ml which was similar to study of Dawood et al (2022) who reported that the average amount of blood lost was 1208.5±227.9 ml and also related with findings of Lohano et al an average of 1155.8 ±350.6 ml of blood was lost per patient. 13,21 In our study mean parity was 4.1±1.3 which was comparable to findings of Lohano et al (2016) 3.41±1.3. 13 Most of patients had middle education i.e.…”
Section: Discussionsupporting
confidence: 86%